Pengaruh Penggunaan Media Sosial Terhadap Perubahan Perilaku Pada Remaja di RW 10 Kelurahan 20 Ilir Timur I Palembang - Putri, Nabila; Ropik, Ainur; Astrid, Gita (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2024)
including sSocial media has become an inseparable trend among society and teenagers. the use of social media can have a positive impact adn negative impacts among adolosescent, one of which is behavior change in adoloescents who are influencend by social media. Adoloscence is a transition from chilhood to adulthood that is prone to negative influences including from social media. the location of the study was conducted in Rw 10 Palembang which has 4 Rt, that is Rt 37,38,39,40. The type of research with questionnaire data collection techniques with likert scale measurements to measure 24 statements and the sample used is 64 respondens who are teenagers in Rw 10. Data analysis techniques used in this study include normality test, reliability test, linearity test, simple regression analysis test, hypothesis test. The result showed the value of the coefficient of determination (R square) 0,664 wgich contains the understanding taht use of free variable social media (Youtube social media use) against bound variables (behavior change) is 65,7% the result of a simple linear analysis obtained Y=4.953+0,907 X, the result of simple linear test of coefficients show that the value of the regression coefficient of social media use of 0,907 which is positive. The result of the t test analysis obtained a calculation of 11, 073 while the t tabel value was 1,669, thus that the calculated value of 11,073 > 1,669 (H0 was rejected and Ha was accepted)